STUDI IMPLEMENTASI KEBIJAKAN REVITALISASI PASAR BULU KOTA SEMARANG - Nova Maulana (Journal of Politic and Government Studies, 2013)
STUDI IMPLEMENTASI KEBIJAKAN REVITALISASI PASAR BULU KOTA SEMARANG(Nova Maulana, Dra. Sulistyowati, M.Si , Drs. Turtiantoro, M.Si*) Jurusan Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro Jl. Prof. H. Soedarto, SH, Tembalang, Semarang, Kode Pos 1269website: http://www.fisip.undip.ac.id email: fisip@undip.ac.id ABSTRACT This study was conducted to explain the policy of the Local Government of Semarang City on the structuring traditional markets in the Bulu Market Semarang. Local government arrange this market because conditions of Bulu that already not optimum enough on its operation. In addition, the location of the market that in Tugu Muda area, that will be make as heritage tourism area, also as central area in Semarang City. The goal of Market Bulu arrangement is for the markets to be orderly, clean, neat, and of course, can fill the good standard of services to consumers and mass. To explain the arrangement of market, this research used descriptive qualitative research methods. Subjects and objects in this study is the Market Service of Semarang City as a representative of the Government, the Regional Technical Implementation Unit (UPTD) Market Area Bulu, Head of Market Bulu, and traders and shoppers. The method of data collection was through interviews and observations with the selection of informants according to the goal of that research. According to data, this policy based on APBD of Semarang City 2012. The main programs are temporary relocations while under construction of new building and collapsing of Bulu’s market old building, also the development of new building. The program plan is the development of Bulu market to be Semi-Modern market. In this process, merchants can accept the terms about this plan and willing to do temporary relocation. But, there are some protests about the limit condition of traders while in relocation place, also there are some fouls that appeared about old building status and the process of AMDAL. Communication provided by the merchants initially poorly understood. High intensity of communication that makes the program can be implemented.Recommendations for future, it takes the approach, communication, coordination and cooperation among the governments with the people (traders), in order to avoid differences in the perception and acceptance of information in the process of policy implementation. Approach taken by the Local Government of Semarang Mahasiswa Ilmu Pemerintahan Fisip Undip 2007  Dosen Ilmu Pemerintahan Fisip Undip  Dosen Ilmu Pemerintahan Fisip Undip2through Market Service of Semarang City more to the approach to the Bulu market traders for aspiration traders considered to be essential and beneficial, rather than policy is top-down. Keywords: The Policy of Semarang Local Government, Implementation Policy, Traditional Market Structuring